Analisis Kualitas Sumber Daya Manusia Dan Komitmen Organisasional Terhadap Kinerja Pendidik Dan Kependidikan - Robi’atul Adawiyah (REVITALISASI : Jurnal Ilmu Manajemen, 2020)
The purpose of this research are: (1) to analyze the effect of quality of human resources on employee’s performance; (2) to analyze the effect of organizational commitment on employee’s performance; and (3) to analyze the influence of quality of human resources and organizational commitment simultaniously on employee’s performance. The subject of this research is SMP POMOSDA Nganjuk Regency. The population of this research are 45 employees. The method used in this research is quantitative approach. Research data obtained by questionnaire, observation, and documentation. The analysis technique used multiple linear regression with F and t test, in testing the research hypothesis. The results showed that, with the fulfillment of validity, reliability and classical assumption test, hypothesis t test proved quality of human resources, and organizational commitment have positive and significant effect on employee’s performance. The F test hypothesis proves that simultaneuosly, multiple regression models strengthened correlational between quality of human resources and organizational commitment toward employee’s performance